Toxicology studies of indole-3-carbinol in F344/N rats and B6C3F1/N mice and toxicology and carcinogenesis studies of indole-3-carbinol in Harlan Sprague Dawley rats and B6C3F1/N mice (gavage studies) - National Toxicology Program (National Toxicology Program technical report series, 2017)
This is a work of the US government and distributed under the terms of the Public Domain.